2005
DOI: 10.1200/jco.2005.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Psychological Distress, and Natural Killer Cell Activity in Ovarian Cancer

Abstract: Psychosocial factors, such as social support and distress, are associated with changes in the cellular immune response, not only in peripheral blood, but also at the tumor level. These relationships were more robust in TIL. These findings support the presence of stress influences in the tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(186 citation statements)
references
References 52 publications
4
176
0
6
Order By: Relevance
“…The relationship between levels of distress and immune factors was assessed in three good studies [18,23,24]. Costanzo et al [18] found that a history of depression and increased depressed mood were associated with higher levels of interleukin-6 in ascitic fluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between levels of distress and immune factors was assessed in three good studies [18,23,24]. Costanzo et al [18] found that a history of depression and increased depressed mood were associated with higher levels of interleukin-6 in ascitic fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Lutgendorf et al [23] found that higher levels of helplessness were associated with higher levels of vascular endothelial growth factor, a pro-angiogenic factor, which is associated with poorer survival. Lutgendorf et al [24] found that increased levels of distress were associated with lower levels of natural killer cells in tumour-infiltrating lymphocytes. Thus, various indices of distress are correlated with biomarkers of important prognostic factors in ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…We used a nonselective b-antagonist (propranolol), as human leukocytes and human tumor cells express both b-1 and b-2 adrenoceptors (50, 51), and as our previous study indicated that the blockade of both receptor systems was more effective than each alone in preventing stress-induced promotion of metastasis (52). Importantly, in the clinical setting of oncologic surgery, the drug regimen used in this study may be even more efficient if initiated a few days before surgery, because etodolac could reduce PGs release by primary tumors (14); propranolol could reduce anxiety (53) and antagonize the excess release of CAs owing to preoperative physiologic and psychologic stress responses (54,55). Together, preoperative use of these drugs can attenuate preoperative suppression of CMI in cancer patients awaiting surgery (10,56).…”
Section: Sectionmentioning
confidence: 99%
“…Social support was assessed by the Attachment subscale of the Social Provisions Scale (SPS-Attachment) (Cutrona and Russell 1987). Based on an a priori hypothesis derived from previous studies of biobehavioral risk factors in ovarian cancer (Costanzo, Lutgendorf et al 2005;Lutgendorf, Sood et al 2005), high psychosocial risk was defined by the presence of a CESD score ≥ 16 and SPS-Attachment score ≤ 15 (the median value). The Beck Depression Inventory (BDI) was also collected for comparison with other published studies, but the CESD served as the primary measure of depression.…”
Section: Depression Social Support and Background Characteristicsmentioning
confidence: 99%